Endogenous retroviral insertions drive non-canonical imprinting in extra-embryonic tissues - Hanna, Courtney W; Pérez-Palacios, Raquel; Gahurova, Lenka; Schubert, Michael; Krueger, Felix; Biggins, Laura; Andrews, Simon; Colomé-Tatché, Maria; Bourc'his, Deborah; Dean, Wendy; Kelsey, Gavin (Genome biology, 2019)
BACKGROUND: Genomic imprinting is an epigenetic phenomenon that allows a subset of genes to be expressed mono-allelically based on the parent of origin and is typically regulated by differential DNA methylation inherited from gametes. Imprinting is pervasive in murine extra-embryonic lineages, and uniquely, the imprinting of several genes has been found to be conferred non-canonically through maternally inherited repressive histone modification H3K27me3. However, the underlying regulatory mechanisms of non-canonical imprinting in post-implantation development remain unexplored. RESULTS: We identify imprinted regions in post-implantation epiblast and extra-embryonic ectoderm (ExE) by assaying allelic histone modifications (H3K4me3, H3K36me3, H3K27me3), gene expression, and DNA methylation in reciprocal C57BL/6 and CAST hybrid embryos. We distinguish loci with DNA methylation-dependent (canonical) and independent (non-canonical) imprinting by assaying hybrid embryos with ablated maternally inherited DNA methylation. We find that non-canonical imprints are localized to endogenous retrovirus-K (ERVK) long terminal repeats (LTRs), which act as imprinted promoters specifically in extra-embryonic lineages. Transcribed ERVK LTRs are CpG-rich and located in close proximity to gene promoters, and imprinting status is determined by their epigenetic patterning in the oocyte. Finally, we show that oocyte-derived H3K27me3 associated with non-canonical imprints is not maintained beyond pre-implantation development at these elements and is replaced by secondary imprinted DNA methylation on the maternal allele in post-implantation ExE, while being completely silenced by bi-allelic DNA methylation in the epiblast. CONCLUSIONS: This study reveals distinct epigenetic mechanisms regulating non-canonical imprinted gene expression between embryonic and extra-embryonic development and identifies an integral role for ERVK LTR repetitive elements.
Keywords: Maternal Inheritance; ženské pohlaví; Endogenous retroviruses (ERVs); myši; H3K27me3; Non-canonical imprinting; Development; Mice; Genomic imprinting; Terminal Repeat Sequences; Retroviridae; genomový imprinting; Embryo; koncové repetice; Animals; maternální dědičnost; histonový kód; zvířata; mužské pohlaví; Male; DNA Methylation; Genomic Imprinting; Placenta; Long terminal repeats (LTRs); Histone Code; metylace DNA; Extra-embryonic; Female; Histone modifications